Addressing Suicidality: Examining Preservice School Counselors' Perceptions of Their Training Experiences. Issue 1 (2nd January 2020) - Springer, Sarah; Paone, Christine Hennigan; Colucci, Jessica; Moss, Lauren J.
ABSTRACT: Suicidality among children and adolescents is a growing public health concern (Osterman et al., 2015). CACREP (2016) and ASCA (2012) include crisis management in their standards and competencies for school counselor education; however, minimal research exists on the nature and perceptions of this training, particularly as it pertains to managing suicide in school communities. The current study shares the results of an exploratory Consensual Qualitative Research (CQR) investigation examining how (n = 10) school counseling students made meaning of their preparatory experiences surrounding suicide prevention, assessment, and postvention. Implications for counselor educators and supervisors will be discussed.